The Singlehood Lifestyle (‘Uzubah): A Socio-Legal Analysis within the Framework of Fiqh al-Munakahat (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2025)
This study examines the phenomenon of the singlehood lifestyle (‘uzubah) in Arsopura Village, Skanto District, Keerom Regency, and evaluates it through the lens of Fiqh al-Munakahat (Islamic jurisprudence on marriage). Although marriage is strongly encouraged in Islamic law as a means of preserving lineage, maintaining social stability, and fulfilling the Maqāṣid al-Sharī‘ah (objectives of Islamic law), a number of residents in Arsopura both men and women choose to remain unmarried into advanced adulthood. Using a qualitative field research design with phenomenological and sociological approaches, data were collected through in-depth interviews, direct observation, and documentation. The analysis reveals that the choice to remain single is predominantly influenced by psychosocial factors such as the comfort of living independently, fear of marital responsibility, distrust arising from negative relational experiences, and economic considerations, reinforced by limited social interaction and weak family influence. These factors although valid from a sociological standpoint do not constitute legitimate ‘udhr shar‘ī (acceptable reason) within the framework of Islamic jurisprudence. From the perspective of Fiqh al-Munakahat and Maqāṣid al-Sharī‘ah, the practice of permanent singlehood in Arsopura contradicts the normative purpose of marriage, especially ḥifẓ al-nasl (the preservation of lineage) and the maintenance of religious and social order. The study concludes that while singlehood may be understood as a personal preference shaped by contemporary social pressures, it does not align with Islamic legal principles. This research underscores the need for community-based religious education, marriage counseling, and socio-religious engagement to harmonize personal autonomy with Islamic marital norms.